Improving The Reading Comprehension through The Use of Think Pair Square at The Second Grade Students of UPT SMPN 1 Srengat Blitar - Suyantri, Suyantri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
Reading plays a very essential role in the context of the teaching of English as a foreign language in Indonesia. In fact, it is one of the supporting skills that students should master if they want to acquire a good mastery of English. Because of its position, reading becomes a very important language skill to be developed in the classroom and consequently the teaching and learning English should be devoted very much for students to develop this receptive skill. . In practice of teaching and learning, reading is a complex process of interaction between writers and readers through printed symbols in the form of texts which requires the readers to master certain skills so that they can catch the intended message in the texts. Texts should be presented in suitable, readable and exploitable ways so that they can be comprehended by their readers . The readers, however, should have reading strategies to apply in order to make reading process run smoothly and faster and finally the intended messages are caught . There are a number of factors affecting the success of reading namely a teacher’s reading competence, students’ competence and the characteristics of the reading materials itself. In second language classes, background knowledge and reading skill constitute the most supporting factors in reading comprehension. This Classroom Action Research (CAR) has an objective to improve the reading comprehension of the second year students of UPT SMPN 1 Srengat Blitar through the use of Think Pair Square method. The subjects of this study were 32 students of class VIII-G SMPN 1 Srengat Blitar in academic year of 2020- 2021, while the object of this study was the technique of teaching reading using Think Pair Square strategy to improve the students’ reading comprehension. The action in the study was conducted in two cycles with four stages of planning, implementing, observing and reflecting on each. Based on the observation on the students’ achievement in cycle two, the students’ average score improved from 79 in the first cycle to 80 in the second cycle . Their classical mastery also improved from 77% in the cycle one to 87% in cycle two. In short, it can be concluded that in the last cycle, students had really made significant progress. Uniquely, the lower and middle students seemed to benefit more the method compared to the upper students indicated by their score in the first and second test. Therefore, English teachers are advisable to adopt the Think Pair square strategy in teaching reading. Besides, they are also encouraged to apply the strategy by using experimental design. The data taken from the observation sheets on the teacher’s and students’ performance done by the collaborator, field note made by the teacher, and mainly the students’ achievement at the last test proved the Think Pair Square strategy to be effective in improving the students’ reading comprehension.